2020
DOI: 10.21608/jpp.2020.122663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Fertilizer and Foliar Spraying with Humic Acid on Productivity of Maize, Soybean and Ear Rot Disease of Maize

Abstract: In the field, two experiments were confirmed in 2017 in addition to 2018 seasons at Sakha Agricultural Researches Station Farm, Agricultural Research Center, Egypt, toward investigate the influence of nitrogen levels (100, 110 and 120 kg N/fed) and spraying with humic-acid levels (without , 2.5, 5.0 and 7.5 g/L) on growth, yield and its attributes, as well ear rot disease of maize under intercropping system of maize and soybean. The field trials were executed in three replicates using split-plot design. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…From these results it can be concluded that for achieving greater yield advantage per unit area from intercropping maize with the tested forage crops, maize plant density must be increased up to 100% of pure stand especially in combination with millet followed by teosinte. Similar results were obtained by previous studies who found that the values of LER was increased more than one by intercropping maize + guar , maize + cowpea (Elsaid et al, 2019), maize + soybean (Abd Rabboh et al, 2020 andWei et al, 2022), teosinte + cowpea (Salem et al, 2019) and millet + cowpea (Mohamed et al, 2020) as compared to their sole croppings. Moreover, other investigators found that the values of LER were increased by increasing plant density of maize intercropped with soybean (Bechem et al, 2018) and with okra (Ijoyah et al, 2012).…”
Section: -4 Land Equivalent Ratio (Ler)supporting
confidence: 91%
“…From these results it can be concluded that for achieving greater yield advantage per unit area from intercropping maize with the tested forage crops, maize plant density must be increased up to 100% of pure stand especially in combination with millet followed by teosinte. Similar results were obtained by previous studies who found that the values of LER was increased more than one by intercropping maize + guar , maize + cowpea (Elsaid et al, 2019), maize + soybean (Abd Rabboh et al, 2020 andWei et al, 2022), teosinte + cowpea (Salem et al, 2019) and millet + cowpea (Mohamed et al, 2020) as compared to their sole croppings. Moreover, other investigators found that the values of LER were increased by increasing plant density of maize intercropped with soybean (Bechem et al, 2018) and with okra (Ijoyah et al, 2012).…”
Section: -4 Land Equivalent Ratio (Ler)supporting
confidence: 91%
“…The variation in maize yield may be attributed to the plant density of maize being lower than recommended when maize intercropped with soybean (2 rows of maize: 2 rows of soybean), but it reached 100% of recommended when maize intercropping with cowpea. This result in line with Abd-Rabboh et al (2020) sole maize had the highest grain yield compared to intercropping culture. A substantial increase in fresh forage yield of clover (fahl) after the legume crop indicated the positive role of legume as the preceding crop.…”
Section: Vii-economic Evaluationmentioning
confidence: 67%